The middle Eocene climatic optimum (MECO): A multiproxy record of paleoceanographic changes in the southeast Atlantic (ODP Site 1263, Walvis Ridge). (8th December 2014) - Boscolo Galazzo, F.; Thomas, E.; Pagani, M.; Warren, C.; Luciani, V.; Giusberti, L.
Abstract The middle Eocene climatic optimum (MECO, ~40 Ma) was a transient period of global warming that interrupted the secular Cenozoic cooling trend. We investigated the paleoceanographic, paleoenvironmental, and paleoecological repercussions of the MECO in the southeast Atlantic subtropical gyre (Ocean Drilling Program Site 1263). TEX86 and δ18O records support an ~4°C increase in surface and deepwater temperatures during the MECO. There is no long‐term negative carbon isotope excursion (CIE) associated with the early warming, consistent with other sites, and there is no short‐term negative CIE (~50 kyr) during the peak of the MECO, in contrast to what has been observed at some sites. This lack of a CIE during the peak of the MECO at Site 1263 could be due to poor sediment recovery or geographic heterogeneity of the δ13C signal. Benthic and planktic foraminiferal mass accumulation rates markedly declined during MECO, indicating a reduction of planktic foraminiferal production and export productivity. Vertical δ13C gradients do not indicate major changes in water column stratification, and there is no biomarker or micropaleontological evidence that hypoxia developed. We suggest that temperature dependency of metabolic rates could explain the observed decrease in foraminiferal productivity during warming. The kinetics of biochemical reactions increase with temperature, more so for heterotrophs than for autotrophs. Steady warming during MECO may have enhanced heterotroph (i.e., foraminiferal) metabolic rates, so that they required more nutrients. These additional nutrients were not available because of the oligotrophic conditions in the region and the lesser response of primary producers to warming. The combination of warming and heterotroph starvation altered pelagic food webs, increased water column recycling of organic carbon, and decreased the amount of organic carbon available to the benthos.